2020
DOI: 10.1021/acs.molpharmaceut.9b01131
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Increases Blood–Brain Barrier Expression of Fatty Acid-Binding Protein 5 and Docosahexaenoic Acid Trafficking into the Brain

Abstract: Brain levels of docosahexaenoic acid (DHA), an essential cognitively beneficial fatty acid, are reduced in Alzheimer's disease (AD). We have demonstrated in an AD mouse model that this is associated with reduced blood−brain barrier (BBB) transport of DHA and lower expression of the key DHA-trafficking protein, fatty acid-binding protein 5 (FABP5). This study focused on assessing the impact of activating peroxisome proliferator-activated receptor (PPAR) isoforms on FABP5 expression and function at the BBB. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Recent research shows that pioglitazone plays a role in facilitating docosahexaenoic acid transport across the blood–brain barrier, which may in part contribute to better cognitive performance. 81 …”
Section: Discussionmentioning
confidence: 99%
“…Recent research shows that pioglitazone plays a role in facilitating docosahexaenoic acid transport across the blood–brain barrier, which may in part contribute to better cognitive performance. 81 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, concerning the usability and principal applications for such in vitro models, the toxicity evaluation of the drugs/compounds is one of the main research points in early drug discovery, where many conditions related to a wide range of concentrations and incubation times must be deeply evaluated. In our study, the impact towards the BBB of different compounds, non-neurotoxic [ 35 , 36 , 37 ] and neurotoxic [ 38 , 39 ], through a wide range of concentrations was assessed. The permeability coefficient of our integrity marker NaF for the endothelium (Pe NaF ) ( Figure 7 ) showed an effect after exposure to high concentrations of neurotoxic compounds such as tamoxifen and rotenone, which were known to disrupt the BBB [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Docosahexaenoic acid (DHA) is an omega-3 PUFA, which serves as a beneficial factor in cognitive function and memory. DHA is sufficiently essential in brain function and its levels are reduced in neurodegenerative diseases such as Alzheimer’s disease ( Low et al, 2020 ). An intracellular carrier protein is required to facilitate the cytosolic trafficking of DHA across the brain endothelial cell to maintain the brain levels of DHA since DHA is not produced by the brain.…”
Section: Biological Functions Of Fabp5mentioning
confidence: 99%
“…In addition, it is also involved in autocrine or paracrine signaling outside the cell, thereby enhancing the effects on systematic glucose, lipid homeostasis, energy metabolism, cell proliferation, and the immunological system. Several studies have reported that FABP5 plays a pivotal role in various diseases including metabolism disorders (e.g., obesity, insulin resistance, and T2DM) ( Yeung et al, 2008 ), skin diseases (e.g., psoriasis) ( Dallaglio et al, 2013 ), neurological diseases (e.g., Alzheimer’s disease) ( Low et al, 2020 ), and carcinoma (e.g., prostate cancer, breast cancer, and cervical cancer) ( Guaita-Esteruelas et al, 2018 ), due to its aberrant expression under pathological conditions. This indicates that FABP5 has tremendous potential in clinical applications.…”
Section: Introductionmentioning
confidence: 99%